Study on Fabrication of Antibacterial Low Molecular Weight Nanochitosan Using Sodium Tripolyphosphate and Hydrogen Peroxide - Tuan Anh Nguyen; Thi Huong Nguyen (Journal of Nanotechnology)
In the study, chitosan was decomposed into low molecular weight chitosan by using different H2O2 concentrations for chain termination, and then chitosan was prepared with different concentrations of tripolyphosphate cations (TPP). We have obtained the following result: the formation of chitosan depends on the concentration of TPP; TPP at low or high concentrations does not react with chitosan to form small chitosan molecules. Properly structured chitosan is only obtained when the mass ratio of chitosan/TPP is 6 : 3. At this rate, when the mass ratio of chitosan/TPP is approximately 6 : 3, there the formed nanochitosan particles have good antibacterial ability against strains of E. coli, M. catarrhalis, and S. aureus. In this work, initially, a successful preparation of a suspension between nasal spray and small chitosan suspension was found at manufacturing ratios: 5 ml nasal spray and 5 ml manufactured chitosan suspension at concentrations of 1 mg/ml, 3 mg/ml, and 5 mg/ml. It proves that the chain termination process by using H2O2 and the creation cross-linking when adding TPP are successful to a certain extent.